HYPERTENSION AND RENIN-ANGIOTENSIN SYSTEM BLOCKERS ARE NOT ASSOCIATED WITH EXPRESSION OF ANGIOTENSIN CONVERTING ENZYME 2 (ACE2) IN THE KIDNEY. (April 2021) - Jiang, Xiao; Eales, James; Scannali, David; Nazgiewicz, Alicja; Prestes, Priscilla; Maier, Michelle; Denniff, Matthew; Xu, Xiaoguang; Saluja, Sushant; Wystrychowski, Wojciech; Zywiec, Joanna; Zukowska-Szczechowska, Ewa; et al.
Abstract : Objective: Angiotensin converting enzyme 2 (ACE2) is the cellular entry point for severe acute respiratory syndrome coronavirus (SARS-CoV-2) – the cause of COVID-19 disease. However, the effect of RAS-inhibition on ACE2 expression in human tissues of key relevance to blood pressure regulation and COVID-19 infection has not previously been reported. Design and method: We examined how hypertension, its major metabolic co-phenotypes and antihypertensive medications relate to ACE2 renal expression using information from up to 436 patients whose kidney transcriptomes were characterised by RNA-sequencing. We further validated some of the key observations in other human tissues and/or a controlled experimental model. Results: Our data reveal increasing expression of ACE2 with age in both human lungs and the kidney. We show no association between renal expression of ACE2 and either hypertension or common types of RAS inhibiting drugs. We demonstrate that renal abundance of ACE2 is positively associated with a biochemical index of kidney function and show a strong enrichment for genes responsible for kidney health and disease in ACE2 co-expression analysis. Conclusions: Our results indicate that neither hypertension nor antihypertensive treatment are likely to alter the expression of the key entry receptor for SARS-CoV-2 in the human kidney. Our data further suggest that in the absence of SARS-CoV-2 infection, kidney ACE2 is most likely nephro-protective but the age-related increase in its expression within lungs and kidneys may be relevant to the risk of SARS-CoV-2 infection.